A new hypogeal species of Oregmopyga Hoy (Hemiptera: Coccoidea: Eriococcidae) from southern California, U.S.A., and a key to species of the genus - Kondo, Takumasa; Gullan, Penny J.; Miller, Douglass R. (Zootaxa, 2004)
A new species of hypogeal eriococcid, Oregmopyga viscosa Kondo sp. nov., is described and illustrated based on the adult female and the second-instar male and female. This species is known from Inyo, Kern, Riverside, San Bernardino, and San Diego counties in southern California, where it lives just below the soil surface on the crown of its host, probably always Hymenoclea salsola Torr. & A. Gray (Asteraceae). A revised key to the adult females of all nine species of Oregmopyga is included.Una nueva especie de erioc ccido subterraneo, Oregmopyga viscosa Kondo sp. nov. (Hemiptera: Coccoidea), se describe e ilustra basandose en la hembra adulta y el segundo estadio de la hembra y el macho. Esta especie ha sido encontrada en los condados Inyo, Kern, Riverside, San Bernardino y San Diego en el sur de California. La especie vive cerca de la superficie en el tallo de su hospedero, siempre siendo probablemente Hymenoclea salsola Torr. & A. Gray (Asteraceae). Se incluye una clave revisada para las hembras adultas de todas las nueve especies de Oregmopyga.